Adaptively Segmenting Angular Sectors for Radar HRRP Automatic Target Recognition. (4th May 2008) - Chen Chen, Bo Bo; Liu Liu, Hongwei Hongwei; Yuan Yuan, Li Li; Bao Bao, Zheng Zheng
Abstract : In this paper the manifold geometry in radar high-resolution range profile (HRRP) is firstly explored, and then, according to the characteristics of target pose sensitivity, a method of adaptively segmenting the aspect sectors is proposed for HRRP recognition through evaluating the curvature of HRRP manifold. Promising experimental results are presented for measured radar data.